HANDLING STUNTING IN TIDORE ISLANDS CITY: ANALYSIS OF SUCCESS FACTORS AND OBSTACLES IN COLLABORATIVE GOVERNANCE: PENANGANAN STUNTING DI KOTA TIDORE KEPULAUAN: ANALISIS FAKTOR KEBERHASILAN DAN HAMBATANDALAM TATA KELOLA KOLABORATIF - Saiful Salim; Umanto Umanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The issue of stunting has received special attention from the government because it has long-term impacts on the productivity and quality of children's human resources. Furthermore, stunting is also a multidimensional health problem encompassing economic, social, cultural, and political dimensions, thus requiring a holistic approach. Tidore Islands City is one of the areas designated as a priority for stunting prevention (2018-2022). Based on socio-economic and geographical factors, Tidore Islands City faces its own challenges; economically it is closely linked to marginalized class groups while geographically it has limited accessibility to the health ecosystem. However, these challenges can be overcome by the government through a collaborative policy strategy, thus successfully reducing stunting cases from 21.3% in 2023 to 16.6% in 2024. Based on this, researchers are interested in understanding more critically the factors that determine success and hinder the handling of stunting through a collaborative governance strategy. Based on this context, this thesis is a descriptive qualitative research or field study. This qualitative research attempts to describe data obtained from the field, literature, and other relevant sources. The results of this study demonstrate various aspects related to stunting cases in Tidore Islands City, including socio-cultural, institutional, and political aspects. Success is largely determined by various factors, including active participation from various elements, data integration and accuracy, routine evaluation and monitoring, training and supervision, transparency and open communication, trust between regional government agencies (OPD), and a single-stop reporting mechanism. Meanwhile, obstacles include limited human resources, access and facilities, duplicate data, asynchronous data, and inaccuracy